Descemet membrane endothelial keratoplasty. Issue 1 (19th May 2015) - Ang, Marcus; Wilkins, Mark R; Mehta, Jodhbir S; Tan, Donald
Abstract : Descemet membrane endothelial keratoplasty (DMEK) allows for selective replacement of damaged endothelial cells, using only donor Descemet's membrane with endothelium. However, early adoption by corneal surgeons has been limited (illustrated by graft registry reports: 0.7% all corneal transplants in the USA; 0.4% in Australia for 2011) due to challenges in donor preparation and surgical technique. Recently, innovative donor preparation techniques may improve availability of pre-stripped DMEK donors from eye banks. The refinement of donor insertion and manipulation techniques has also improved outcomes and reduced graft detachment rates—still, the most common postoperative complication following DMEK. Randomised studies are needed to compare clinical practices and surgeon preferences, such as intraoperative use of long-acting gas, early versus late intervention of graft detachments and postoperative steroid management. A review of current literature reveals that most publications to date are reports from similar study cohorts by surgeons who pioneered and advocate this technique. Thus, more long-term clinical studies in other tertiary centres are required in order to confirm if the purported advantages of DMEK such as improved visual outcomes and reduced graft rejection are replicable among most corneal surgeons.